2012
DOI: 10.1007/s11999-011-2037-1
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Preferred Articulating Spacer Technique for Infected Knee Arthroplasty?: A Preliminary Study

Abstract: Background Periprosthetic infection in TKA is a devastating and challenging problem for both patients and surgeons. Two-stage exchange arthroplasty with an interval antibiotic spacer reportedly has the highest infection control rate. Studies comparing static spacers with articulating spacers have reported varying ROM after reimplant, which could be due to differences in articulating spacer technique. Questions/purposes We therefore determined whether one of three articulating spacer techniques was superior in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…By contrast the studies of Hirakawa [40] and Kalore [45] identified much higher re-infection rates of 25% and 28% respectively. These rates are among the highest of the studies identified by this systematic review.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…By contrast the studies of Hirakawa [40] and Kalore [45] identified much higher re-infection rates of 25% and 28% respectively. These rates are among the highest of the studies identified by this systematic review.…”
Section: Resultsmentioning
confidence: 75%
“…Eight studies of between 50 and 60 patients reported reinfection rates of 4% [52], 7% [32], 8% [33], 12% [59] and [70], 25% [40] and 28% [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Emerging data suggest that articulating spacers offer comparable rates of infection eradication, improved postoperative flexion, and easier surgical exposure when compared with static spacers, albeit at a higher cost and complexity [8,10,14,20,23]. By contrast, potential advantages of static spacers include lower cost, ease of implantation, and facilitation of wound immobilization whereby tenuous soft tissues, bone deficiency, and extensor mechanism compromise may be better managed.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to an NFC spacer, the autoclaved original femoral component is cost-effective11); however, we are concerned about reusing an implant designed for single use only19).…”
Section: Discussionmentioning
confidence: 99%